Genetic background of idiopathic pulmonary fibrosis. (May 2013) - Santangelo, Simona; Scarlata, Simone; Zito, Anna; Chiurco, Domenica; Pedone, Claudio; Incalzi, Raffaele Antonelli
Idiopathic pulmonary fibrosis (IPF) is a chronic, progressive lung disease characterized by progressive fibrosing interstitial pneumonia. The histological pattern, which displays dense fibrosis with active areas of fibroblastic proliferation, suggests a pathogenetic role of aberrant response to healing of multiple microscopic, repeated alveolar epithelial injuries. Although the exact etiology of the disease is still under investigation, several studies suggest that a combination of genetic and environmental factors may play a causal role. The aim of this review is to describe the genetic background of IPF, reporting the latest advancements made possible by genomic techniques that allow a high-throughput analysis and the identification of target genes implicated in IPF. This information may help to clarify pivotal aspects on prognosis and diagnosis, and may help to identify potential targets for future therapies.